Serum-induced recovery of proliferative capacity and differentiation potential in aged dental pulp stem cells - Cho-Yeon Park; Joung-Ho Moon; Sang-Man Lee; Eun-Hye Lee; Joo-Young Park; Sun-Young Kim (Stem Cells Translational Medicine, 2026)
Abstract Background Aging impairs the proliferative, survival, and differentiation capacities of dental pulp stem cells (DPSCs), thereby limiting their regenerative potential. This study systematically investigated whether high-serum preconditioning could promote serum-induced recovery of age-associated functional decline in rat and human DPSCs. Methods Young, older, and high-serum-conditioned DPSCs were compared using in vitro assays assessing proliferation, survival, colony-forming efficiency, and multilineage differentiation, together with in vivo functional regeneration models and transcriptomic profiling of human DPSCs. Results High-serum preconditioning significantly enhanced proliferation and colony-forming efficiency in older DPSCs and restored osteogenesis and neurogenesis through serum-induced recovery, approaching the levels of young cells. In vivo, transplantation of high-serum-conditioned DPSCs resulted in organized axonal regeneration accompanied by compact myelin formation, as well as improved bone regeneration in calvarial defect models, demonstrating functional recovery beyond in vitro outcomes. Human DPSCs cultured under high-serum conditions similarly exhibited increased proliferation, viability, and lineage-specific differentiation capacity while maintaining stable expression of mesenchymal stem cell markers. Transcriptomic analysis revealed extensive remodeling under high-serum conditions, including activation of stemness- and cell cycle-related gene programs and suppression of senescence-associated transcripts. However, global gene expression patterns indicated only partial convergence toward a youthful transcriptional state rather than complete rejuvenation. Conclusions High-serum preconditioning promotes serum-induced recovery and partially restores the regenerative competence of older DPSCs through reconfiguration of functional and molecular programs without full reversion to a youthful state. This study provides preliminary insight into serum-induced recovery and a framework for identifying serum-derived factors for future stem cell-based regenerative applications.